2022
DOI: 10.3390/machines10050287
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Implementation of the Single Minute Exchange of Die Methodology in an Agroindustry through Action Research

Abstract: This work aims to implement and analyze the effect of the Single Minute Exchange of Die (SMED) implementation in the bean packaging operation in a company in east Minas Gerais, Brazil. Design/Methodology/Approach: The research methodology used was action research. Two cycles of action research were conducted; the first to carry out phase one of SMED, and the second to execute phases two and three. Originality/Research gap: There are few studies on the application of Lean Manufacturing tools in agroindustry. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The analysis showed that some studies stand out and can contribute to developing technologies through access to information through open innovation. Using sensors and cloud computing would efficiently improve production processes and prioritize this proposal in future studies [72]. A framework was proposed and evaluated in actual conditions on a farm, remotely monitoring and controlling the precision agriculture installation systems [73].…”
Section: Autonomous and Collaborative Robotsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis showed that some studies stand out and can contribute to developing technologies through access to information through open innovation. Using sensors and cloud computing would efficiently improve production processes and prioritize this proposal in future studies [72]. A framework was proposed and evaluated in actual conditions on a farm, remotely monitoring and controlling the precision agriculture installation systems [73].…”
Section: Autonomous and Collaborative Robotsmentioning
confidence: 99%
“…[ [70][71][72]78,82] The main challenges are process orientation, standardization, data communication and security, and knowledge transfer. Many new technologies are still in the testing phase, requiring simultaneous engineering practices for evaluations.…”
Section: Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing changeover time leads to a reduction of lead time and ensuring and enhancing competitiveness, as manufacturing loss is related to loss of competitiveness (Malindzakova et al, 2021). Benefits of implementing SMED include cost and waste reduction, increased production capacity and flexibility of the equipment, increased machine efficiency and customer satisfaction (Ribeiro et al, 2022). Thanks to increasing the availability and the efficiency of the production line, SMED allows for increasing the Overall Equipment Effectiveness (Otero & Lopes, 2018;Suryaprakash et al, 2021;Pattaro Jr. et al, 2022).…”
Section: Single Minute Exchange Of Diementioning
confidence: 99%
“…In this article, we focus on tools such as Single Minute Exchange of Die (SMED) and Total Productive Maintenance (TPM), which are aimed at managing machines and equipment, reducing waste and lead time. Short lead times mean higher flexibility and improved competitive position (Malindzakova et al, 2021;Ribeiro et al, 2022). These tools were chosen concerning their impact on competitiveness and at the same time with regard to the focus of the author's collective.…”
Section: Introductionmentioning
confidence: 99%